Workshop Report: International Workshop of the Knowledge Action Group of the Global Alliance for Climate-Smart Agriculture - Matteoli, F; Mason, M; Dinesh, Dhanush (2015)
This report summarizes the proceedings of the “International Workshop of the Knowledge Action Group,” held in Montpellier, March 15th, 2015, organized by CCAFS, FAO, and CIRAD. The workshop brought together participants from Governments, research institutions, farmer organizations, civil society organizations, and the private sector to determine the knowledge priorities for Climate-Smart Agriculture and partnerships to make these priorities possible. The priorities and outputs identified at the workshop formed inputs into the Knowledge Action Group’s work plan for its inception year. The workshop provided background on the role that the Global Alliance for Climate-Smart Agriculture plays in developing a knowledge base for Climate-Smart Agriculture, and provided participants insights into how the Knowledge Action Group of the Alliance is governed and its activities to date. Discussions at workshop focused on the five priority work areas of the Knowledge Action Group (1. technical interventions and practices in CSA; 2. evidence base of CSA; 3. support, services and extension for CSA; 4. inclusive knowledge systems for CSA, and 5. integrated planning and monitoring for CSA). Participants identified the priority outputs for the inception year and partnerships to achieve these outputs. The workshop provided a platform for participants to share ideas, knowledge, approaches and resources, fostering stronger partnerships between organizations.